2016
DOI: 10.1073/pnas.1613818113
|View full text |Cite
|
Sign up to set email alerts
|

Rippling ultrafast dynamics of suspended 2D monolayers, graphene

Abstract: Here, using ultrafast electron crystallography (UEC), we report the observation of rippling dynamics in suspended monolayer graphene, the prototypical and most-studied 2D material. The high scattering cross-section for electron/matter interaction, the atomicscale spatial resolution, and the ultrafast temporal resolution of UEC represent the key elements that make this technique a unique tool for the dynamic investigation of 2D materials, and nanostructures in general. We find that, at early time after the ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 52 publications
2
46
0
Order By: Relevance
“…4j and k. Here, no clear transition from ABC to ABA was observed, although there were some alternations in the ABA area (dark fringes in the bottom part in Fig. 4k), which can also be an effect of enhanced rippling in graphene after photo-excitation [28].…”
Section: In-situ Electron Microscopy Experimentsmentioning
confidence: 83%
“…4j and k. Here, no clear transition from ABC to ABA was observed, although there were some alternations in the ABA area (dark fringes in the bottom part in Fig. 4k), which can also be an effect of enhanced rippling in graphene after photo-excitation [28].…”
Section: In-situ Electron Microscopy Experimentsmentioning
confidence: 83%
“…2C). The time constant of τ 1 = 2.9 ± 1.2 ps shows characteristic time of the in-plane lattice expansion, as a result of an in-plane acoustic wave propagation 22,23 . Comparing with the freestanding multilayer samples 18,19 , the lack of oscillatory Bragg peak shift suggests an overdamped mode that may result from the interaction with the substrate.…”
Section: In-plane Structural Dynamicsmentioning
confidence: 95%
“…(right) Integrated intensity values for the ground state {10l} CTR, obtained by integration at different out-of-plane momentum transfer values q z . used to characterize in-plane structural dynamics of monolayer 2D materials 22,23 , while the out-of-plane structural dynamics of a monolayer crystal was only inferred 23 . Comparing with ultrafast electron diffraction, ultrafast x-ray diffraction has been an indispensable tool for studying structural dynamics in thin films, providing evidence on non-thermal structural response in transition metal dichacogenides 24 and electron-phonon coupling in superconducting FeSe 14 .…”
mentioning
confidence: 99%
“…22,23 The timescale for generation of flexural ZA phonons (out of graphene plane atomic vibrations) and dynamic rippling is in the order of 50 ps. 24 Detailed theoretical considerations by Panizon et al 2 have shown that transfer of momentum from graphene to adsorbed Au NCs is carried out by flexural ZA phonons or by and the (220) peaks (red and blue data-points, respectively) and biexponential fittings (solid lines). The two data-sets presented in this figure disentangle the two processes that affect peak decay dynamics, namely, lattice heating (a) and disorientation of NCs (b).…”
Section: Femtosecond Electron Diffractionmentioning
confidence: 99%